Haemophilus somnus Induces Apoptosis in Bovine Endothelial Cells In Vitro - Sylte, Matt J. (American Society for Microbiology, 2001)
Haemophilus somnus causes pneumonia, reproductive failure, infectious myocarditis, thrombotic meningoencephalitis, and other diseases in cattle. Although vasculitis is commonly seen as a result of systemic H. somnus infections, the pathogenesis of vascular damage is poorly characterized. In this study, we demonstrated that H. somnus (pathogenic isolates 649, 2336, and 8025 and asymptomatic carrier isolates 127P and 129Pt) induce apoptosis of bovine endothelial cells in a time- and dose-dependent manner, as determined by Hoechst 33342 staining, terminal deoxynucleotidyl transferase-mediated dUTP-FITC nick end labeling, DNA fragmentation, and transmission electron microscopy. H. somnus induced endothelial cell apoptosis in as little as 1 h of incubation and did not require extracellular growth of the bacteria. Viable H. somnus organisms induced greater endothelial cell apoptosis than heat-killed organisms. Since viable H. somnus cells release membrane fibrils and blebs, which contain lipooligosaccharide (LOS) and immunoglobulin binding proteins, we examined culture filtrates for their ability to induce endothelial cell apoptosis. Culture filtrates induced similar levels of endothelial cell apoptosis, as did viable H. somnus organisms. Heat inactivation of H. somnus culture filtrates partially reduced the apoptotic effect on endothelial cells, which suggested the presence of both heat-labile and heat-stable factors. We found that H. somnus LOS, which is heat stable, induced endothelial cell apoptosis in a time- and dose-dependent manner and was inhibited by the addition of polymyxin B. These data demonstrate that H. somnus and its LOS induce endothelial cell apoptosis, which may play a role in producing vasculitis in vivo.